Synthesis and Antibacterial Activity of Some New Phenothiazine Derivatives - Pawan Kumar Swarnkar; P. Kriplani; G. N. Gupta; K. G. Ojha (E-Journal of Chemistry)
A series of some new phenothiazine derivatives were synthesized with the objective for evaluation as antimicrobials. The title compounds were prepared by a five step synthesis scheme. 2-Amino-6-substituted benzothiazoles (1) on diazotization afford 6-substituted benzothiazolyl-2-diazonium chlorides (2). Reaction of 2 with cold solution of β-naphthol in dilute NaOH furnishes α-(2-diazo-6-substituted benzothiazolyl)- β-sodionaphthoxides (3) which on acidification with concentrated HCl gives α-(2-diazo-6-substituted benzothiazolyl)-β-naphthols (4). Reaction of 4 with p-substituted anilines gives α-(2-diazo-6-substituted benzothiazolyl)-β-(p-substituted anilino) naphthalenes (5). This synthesis besides by using conventional methods was also attempted using microwave. Fusion of 5 with sulphur in presence of iodine results in α-(2-diazo-6-substituted benzothiazolyl)-6- substituted [2, 3-b] benzophenothiazines(6). The structures of all these compounds have been supported by elemental analysis and their spectral studies. All synthesized compounds were tested for their antibacterial activity using standard drugs.